Omnino Undergraduate Research Journal, Volume 7, January 1, 2018. - Valdosta State University (Valdosta State University, 2018)
Introduction 7 by Dr. Anne Greenfield The East China Sea Dispute: A Case Study 8 By Sean P Jankowski Troubled Seas and Scattered Blossoms: Nature Images in Elegiac Anglo-Saxon and Japanese Poetry of the Medieval Period By Audrey Whittle Forensic Interviewing in Child Sexual Abuse Cases By Jacob W Highsmith 31 in a Billion: An Analysis of the Adoption of Voter ID Laws 44 By Obediah Hall In Search of a New Life: Ildara and “The Red Stockings” [English Version] By Susanna Peonia En búsqueda de una vida nueva: Ildara y “Las medias rojas” [Versión en español] Por Susanna Peonia “First in Freedom” State Passes Bill to Sideline Transgender Freedom: An Analysis of Legislative Voting Behavior on House Bill 2 By Kelah M Hendon Lewdness in The Country Wife (1675) By Kimberly Cannon Effect of Sexual Orientation and Length of a Relationship on Perceptions of Rape By Amelia M Lively
Valdosta State University (2018) "Omnino Undergraduate Research Journal," vol.07. (Valdosta State University, 2018). Downloaded from Web (20180104) https://issuu.com/vsuenglish/docs/volume_7
Keywords: College students' writings; Research; Periodicals; Interdisciplinary research